Giant cell tumor in adipose package Hoffa. Issue 1 (31st January 2017) - Etcheto, H. Rivarola; Escobar, G.; Blanchod, C. Collazo; Palanconi, M.; Zordan, J.; Salinas, E. Alvarez; Autorino₁, Carlos
Tumors of adipose Hoffa package are very uncommon, with isolated cases reported in the literature. His presentation in pediatric patients knee is exceptional. The most frequently described tumors are benign including vellonodular synovitis. The extra-articular localized variant there of is known as giant cell tumor of the tendon sheath. It is characterized by locally aggressive nature, and has been described in reports of isolated cases. Objective: A case of giant cell tumor of the tendon sheath in adipose presentation package Hoffa in pediatric patients is presented in this paper. Methods: male patient eleven years with right knee pain after sports practice was evaluated. Physical examination, showed limited extension -30º, joint effusion, stable negative Lachman maneuver without peripheral knee laxity. MRI hyperintense on tumor is observed in T2 and hypointense on T1 homogeneous and defined edges content displayed prior to LCA related to adipose Hoffa package. Results: The tumor specimen was obtained and histopathology is defined as densely cellular tissue accumulation of xantomisados fibrocollagenous with histiocytes and multinucleated giant cells, compatible with giant cell tumor of tendon sheath. Conclusion: The presentation of giant cell tumors of the tendon sheath in Hoffa fat pad is exceptional. However, his suspicion allows adequate preoperative surgical planning, as a whole resection is the only procedure that has been shown to decrease the rate of recurrence of this disease.